The concept of tourism in the Holy Quran: An objective study - Mohamed, Nussaiba Abdelrahim (Journal of Islamic Sciences, 2021)
Tourism is one of the things that society is hardly devoid of, and it is one of the things that benefit society, as well as it has goals and objectives that distinguish it, but in spite of that it lacks a statement of some of what surrounds it and correct some understanding of it, and a statement of its purposes and the desired benefits, and enumerate Its forms, which vary according to time, place and reason, so we find that the Noble Qur’an mentioned the term tourism in a number of its verses, as well as some terms that carry its meaning and indicate it, such as striking on the ground, traveling and walking from one place to another place, all of which means movement for a purpose and demand, and man reaps from There are many outcomes behind this, as it is in its scientific and linguistic sense indicating that it is one of the permissible matters with its various legitimate reasons bearing upon it. Through this research, we want to show its benefits, purposes, and judgment according to the analytical and deductive approach through the interpretation of the verses of the Holy Quran in which the term tourism and its synonyms were mentioned, and what these verses give him evidence and clarify the instructions and judgment that he brought about, and motivate them to tourism on earth and encourage it to a degree It amounts to linking it to the faith in terms of contemplating the creation of God, calling to God, contemplation, drawing lessons and lessons, and achieving the content of the message reaching the whole world, and among the most prominent results of this study is that it concluded with a number of items, namely: that the acquisition of livelihood and knowledge is guaranteed by the Creator, the Almighty, but Diligence and efforts must be made to obtain it in all permissible forms. Also, contemplation and contemplation of the creatures of God Almighty and standing on the effects of nations are among the things that strengthen the bonds of the servant’s attachment to his Creator. Whereas, the Islamic religion does not prevent recreation and recreation in a way that suits Islamic principles, but rather makes it one of the inevitable tasks so that souls are not tired and resorted to despondency and despair because of the hardships and worries they encounter in the course of their lives. Finally, the economic tourism returns are well known to us, as it brings abundant benefit to the country and its residents by raising the standard of living as it is a source of income that has a large return that develops the economy.